The effect of individual morality, information asymmetry and organizational culture on the tendency of accounting fraud - Ni Putu Yunika Tiffany Rachma Sari; Ni Luh Putu Sri Purnama Pradnyani; Luh Diah Citra Resmi Cahyadi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
This study aims to determine the effect of individual morality, information asymmetry and organizational culture on fraud tendencies. This research was conducted at LPD in Kerambitan District. The research method used in this study is a quantitative research method with primary data obtained from questionnaire data as measured by a Likert scale. The population of this study were LPD employees in Kerambitan District, while the sampling method used was purposive sampling with a total sample of 114 respondents. Data analysis used multiple linear regression using SPSS 26. Based on the results of the study, it was shown that individual morality has a negative influence on the tendency of accounting fraud. Information asymmetry has a positive effect on the tendency of accounting fraud. Organizational culture has a negative effect on the tendency of accounting fraud. The advice that researchers can give is to internal supervisory bodies (panureksa) give warnings or sanctions to employees who have bad morals and do not apply organizational culture and always supervise the preparation of financial reports to minimize fraud in the preparation of financial reports.